Eupatilin, a Major Flavonoid of Artemisia, Attenuates Aortic Smooth Muscle Cell Proliferation and Migration by Inhibiting PI3K, MKK3/6, and MKK4 Activities - Son, Joe Eun; Lee, Eunjung; Seo, Sang Gwon; Lee, Jihoon; Kim, Jong Eun; Kim, Jiyoung; Lee, Ki Won; Lee, Hyong Joo (Planta Medica, 2013)
Eupatilin, a major flavonoid of plants in the genus Artemisia, has been shown to exhibit anti-inflammatory, anti-oxidative, and anti-tumor effects. However, the potential anti-atherogenic effects of eupatilin and any underlying mechanisms have not been investigated. In the present study, we sought to determine the effects of eupatilin on phenotypes induced by the growth factor PDGF-BB in human aortic smooth muscle cells. Here we show that aortic sprouting as well as PDGF-BB-induced proliferation and migration of human aortic smooth muscle cells were significantly inhibited by eupatilin. We found that eupatilin inhibited PI3K activity, causing a direct effect on phosphorylation of the downstream kinases Akt and p70S6K. In parallel, eupatilin also inhibited the phosphorylation of MKK3/6-p38 MAPK and the MKK4-JNK pathway. Moreover we found that eupatilin exhibited stronger inhibition effects on PDGF-BB-induced proliferation and migration of human aortic smooth muscle cells than PI3K, p38 MAPK, and JNK pathway inhibitors. Taken together, our results indicate that eupatilin is a potent anti-atherogenic agent that inhibits PDGF-BB-induced proliferation and migration in HASMCs as well as aortic sprouting, which is likely mediated through the attenuation of PI3K, MKK3/6, and MKK4 activation.
Keywords: eupatilin; aortic smooth muscle cells; platelet-derived growth factor; PI3K; MAPKs; atherosclerosis